One-pot thiol–amine bioconjugation to maleimides: simultaneous stabilisation and dual functionalisation. Issue 42 (2nd October 2020) - Wall, Archie; Wills, Alfie G.; Forte, Nafsika; Bahou, Calise; Bonin, Lisa; Nicholls, Karl; Ma, Michelle T.; Chudasama, Vijay; Baker, James R.
Abstract : An alternative approach to maleimide conjugate stabilisation is presented, by the consecutive addition of a thiol and an amine to dibromomaleimides. The amine serves to simultaneously deactivate the maleimide and enable dual functionalisation. Abstract : Maleimide chemistry is widely used in the site-selective modification of proteins. However, hydrolysis of the resultant thiosuccinimides is required to provide robust stability to the bioconjugates. Herein, we present an alternative approach that affords simultaneous stabilisation and dual functionalisation in a one pot fashion. By consecutive conjugation of a thiol and an amine to dibromomaleimides, we show that aminothiomaleimides can be generated extremely efficiently. Furthermore, the amine serves to deactivate the electrophilicity of the maleimide, precluding further reactivity and hence generating stable conjugates. We have applied this conjugation strategy to peptides and proteins to generate stabilised trifunctional conjugates. We propose that this stabilisation-dual modification strategy could have widespread use in the generation of diverse conjugates.